Requirement for CDK6 in MLL-rearranged acute myeloid leukemia - Placke, Theresa; Faber, Katrin; Nonami, Atsushi; Putwain, Sarah L.; Salih, Helmut R.; Heidel, Florian H.; Krämer, Alwin; Root, David E.; Barbie, David A.; Krivtsov, Andrei V.; Armstrong, Scott A.; Hahn, William C.; et al. (Blood, 2014)
Chromosomal rearrangements involving the H3K4 methyltransferase mixed-lineage leukemia (MLL) trigger aberrant gene expression in hematopoietic progenitors and give rise to an aggressive subtype of acute myeloid leukemia (AML). Insights into MLL fusion-mediated leukemogenesis have not yet translated into better therapies because MLL is difficult to target directly, and the identity of the genes downstream of MLL whose altered transcription mediates leukemic transformation are poorly annotated. We used a functional genetic approach to uncover that AML cells driven by MLL-AF9 are exceptionally reliant on the cell-cycle regulator CDK6, but not its functional homolog CDK4, and that the preferential growth inhibition induced by CDK6 depletion is mediated through enhanced myeloid differentiation. CDK6 essentiality is also evident in AML cells harboring alternate MLL fusions and a mouse model of MLL-AF9–driven leukemia and can be ascribed to transcriptional activation of CDK6 by mutant MLL. Importantly, the context-dependent effects of lowering CDK6 expression are closely phenocopied by a small-molecule CDK6 inhibitor currently in clinical development. These data identify CDK6 as critical effector of MLL fusions in leukemogenesis that might be targeted to overcome the differentiation block associated with MLL-rearranged AML, and underscore that cell-cycle regulators may have distinct, noncanonical, and nonredundant functions in different contexts. •CDK6 is a critical effector of MLL fusions in myeloid leukemogenesis.•Genetic and pharmacologic inhibition of CDK6 overcome the differentiation block associated with MLL-rearranged AML.